2012
DOI: 10.1186/1471-2431-12-111
|View full text |Cite
|
Sign up to set email alerts
|

A 12-week after-school physical activity programme improves endothelial cell function in overweight and obese children: a randomised controlled study

Abstract: BackgroundEndothelial dysfunction is associated with childhood obesity and is closely linked to the amount and function of endothelial progenitor cells. However, it remains unclear whether endothelial progenitor cells increase with after-school exercise in overweight and obese children. The purpose of this study was to investigate the effects of an after-school exercise programme on endothelial cell function in overweight and obese children.MethodsA total of 29 overweight/obese children (12.2 ± 0.1 years) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 44 publications
3
56
0
12
Order By: Relevance
“…A significant rise in EPCs had been observed previously in obese adolescents after 12 weeks of exercise training. 24 The EPC phenotype, however, differed from what is currently accepted. 22 In accordance with the latest recommendations, Walther et al demonstrated that 1 year of additional exercise during school time is an effective means to markedly increase the number of circulating CD45low/CD34+/KDR+ EPC.…”
Section: Discussionmentioning
confidence: 83%
“…A significant rise in EPCs had been observed previously in obese adolescents after 12 weeks of exercise training. 24 The EPC phenotype, however, differed from what is currently accepted. 22 In accordance with the latest recommendations, Walther et al demonstrated that 1 year of additional exercise during school time is an effective means to markedly increase the number of circulating CD45low/CD34+/KDR+ EPC.…”
Section: Discussionmentioning
confidence: 83%
“…37,40,41,57 Subjects participating in interventions with vitamin supplements, exercise, and diet displayed greater improvements in PWV (3.7±0.1 versus 4.1±0.1 m/s; P<0.05) than those only involved in exercise and dieting (no significant reduction in PWV). 59 National Cholesterol Education Program-II diet with vitamin-C and E supplements showed improved FMD from baseline (9.5±4.2 versus 5.7±2.9%; P<0.001); however, there was no significant alteration in FMD from diet alone. 57 Another trial demonstrated that exercising and dieting subjects developed better FMD alterations from baseline (8.0±1.8 versus 6.8±2.0%; P<0.0001) than those only dieting (7.5±1.9 versus 6.9±2.0%; P<0.002).…”
Section: Multiple Interventionsmentioning
confidence: 69%
“…The majority of these studies demonstrated a significant improvement in at least 1 noninvasive measure of vascular health, 27,29,35,37,39,42,47,55,58,59 with 6 showing a significant improvement in at least 1 marker of inflammation or oxidative stress. 32,35,37,47,55,58 In the interventions that did not demonstrate a significant improvement in any vascular health index, 28,32,33,36,54 all but 1 did not result in a significant change in inflammatory or oxidative stress biomarkers.…”
Section: Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have examined the effects of long-term physical activity interventions in children and both demonstrated an increase in HSPC quantity with increased physical activity. 45,46 Additionally, in young healthy adults, exercise training increased HSPC quantity, and the effects of exercise were augmented by training under hypoxic conditions. 47 These data suggest that in response to a properly designed training program under wellcontrolled conditions, HSPC content may indeed increase with exercise training.…”
Section: Article In Pressmentioning
confidence: 98%